2021
DOI: 10.1111/jam.15131
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotyping and genotyping of extensively drug‐resistant (XDR) Salmonella sp. isolated from clinical samples of Lahore, Pakistan

Abstract: Aims Antibiotic resistance is a major problem in Salmonella enterica serovar Typhi. The objective of this study was to evaluate the prevalence of XDR Salmonella among local population of Lahore and genotyping of isolates for antibiotic‐resistant genes. Methods and Results A total of 200 blood samples from suspected typhoid fever patients were collected. One hundred and fifty‐seven bacterial samples were confirmed as Salmonella Typhi and 23 samples were confirmed as Salmonella Paratyphi after biochemical, serol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“… 28 Regarding resistance determinants of third-generation cephalosporin, in our study we reported different types of CTX-M for the very first time. Many studies have reported high prevalence of bla CTX-M-15 in XDR isolates 5 , 41 , 44–46 but in our study other types were also identified. In our study bla CTX-M-U was the most frequent gene present in 63.3% XDR isolates followed by bla CTX-M-15 (39.3%).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“… 28 Regarding resistance determinants of third-generation cephalosporin, in our study we reported different types of CTX-M for the very first time. Many studies have reported high prevalence of bla CTX-M-15 in XDR isolates 5 , 41 , 44–46 but in our study other types were also identified. In our study bla CTX-M-U was the most frequent gene present in 63.3% XDR isolates followed by bla CTX-M-15 (39.3%).…”
Section: Discussioncontrasting
confidence: 43%
“…The ampC gene, which has a 47% prevalence, was the most common resistance gene, followed by the gyrA, catA1, tet(A), aac (3)-la, qnrS, bla NDM-1 , and bla CTX-M-15 genes in isolates with 45,40,21,6,18,3,11,6, and 2%, respectively. 44 This study did not report presence of bla TEM-1 or any other variants in their XDR isolates.…”
mentioning
confidence: 69%
“…will be an added threat. Preliminary studies of the potential treatment of SARS-CoV-2 with azithromycin [42] have resulted in irrational use of azithromycin even in patients with suspected COVID-19. Under the current scenario, unprecedented use of azithromycin in Pakistan (unpublished data) increases the likelihood of azithromycin being insensitive to S. Typhi XDR.…”
Section: Discussionmentioning
confidence: 99%